A genealogy of postmodern subjects: Discourse analysis and late capitalism. (June 2015) - Hayter, Donna; Hegarty, Peter
Critiques of psychology's complicities with the ideological workings of capitalism have focused on psychologies developed prior to the 1980s, against which discursive and postmodern theories are often positioned as liberatory or revolutionary. Critical Marxist theory and anthropologies of finance are used here to frame a genealogy of Jonathan Potter and Margaret Wetherell's seminal text of discourse analysis Discourse and Social Psychology that challenges this narrative. We focus on the ontological differences between Potter and Wetherell and the modernist theorists of language and social order that they cite: Noam Chomsky, John Austin, and Harold Garfinkel. We argue that the ontology of both personhood and research within this text converged with the subjectivities constituted and required by late capitalism that dislocate and dispense notions of individual accountability upon which earlier modes of capitalism depended.